OC-039 Improving Quality In A National Intestinal Failure Unit: Greater Efficiency, Improved Access, Reduced Mortality. (9th June 2014) - Donaldson, E; Taylor, M; Abraham, A; Carlson, G; Fletcher, O; Jacqui, V; Teubner, A; Lal, S
Abstract : Introduction: In 2010, there was a significant waiting list for admission to the Intestinal Failure Unit (IFU) at Salford, one of two current nationally-accredited centres. There had also been a steady increase in referrals to the IFU (89 patients in 2005; 152 patients in 2012) and the number of established patients requiring home parenteral nutrition (HPN) (135 patients in 2005; 206 patients in 2012). The impact of the long waiting list for these complex patients was that patient deaths occurred in those awaiting admission. Furthermore, the 'Strategic Framework for IF and HPN Services' in England had earlier highlighted the need for services to 'foster equity of access'. 1 The SRFT IFU team therefore conducted a rigorous assessment of its processes in order to improve patient flow and access to the IFU. The primary aim was to reduce inpatient length of stay (LOS) by 10%. Methods: We employed continuous improvement methodology, utilising the Model for Improvement and running sequential Plan-Do-Study-Act cycles. In addition to the key flow data, such as LOS and referral times, process data were collected, including time to intravenous feeding line insertion, time to radiology studies etc., when looking to streamline specific areas of practice. Data were analysed using statistical process control charts produced using QI Macros (KnowWare International, INC.). Statistically significant shifts were determined 'a priori' according to standard operating principals for special cause variation. 2 Results: Process improvements yielded a 20.8% reduction in average length of stay on the IFU from 55.7 to 44.1 days and a reduction of 70.7% in the average length of time spent on the waiting list for admission from 65.1 to 19.1 days. These changes were associated with concomitant reduction in 30-day readmission rates from 12.1 to 4.5% and early suggestions of reduced waiting list mortality. The number of inpatient deaths did not increase; indeed, there was a sustained increase in the number of complete discharge episodes between inpatient deaths (mean increase from 13 to 44). Conclusion: A quality improvement model is an effective means of enhancing the efficiency of a large National centre dealing with complex medical and surgical patients. Improvements in inpatient efficiency can reduce waiting times for admission, thus improving access and reducing waiting list mortality. The improvements in efficiency can be achieved without compromising patient safety. References: 1 Strategic Framework for Intestinal Failure and Home Parenteral Nutrition Services for Adults in England 2008 2 Langley, G et al . 2009. The improvement guide: a practical approach to enhancing organizational performance. John Wiley & Sons Disclosure of Interest: None Declared.